Estimates for the Kolmogorov widths of the Nikol’skii–Besov–Amanov classes in the Lorentz space - Akishev, G. (Pleiades Publishing, 2017)
The Lorentz space with anisotropic norm of periodic functions of several variables is considered. Estimates for the Kolmogorov widths of the Nikol’skii–Besov–Amanov classes in the Lorentz space with anisotropic norm are found.
Keywords: Lorentz space; Nikol’skii–Besov class; Kolmogorov width